Role of the ubiquitin-like protein Urm1 as a noncanonical lysine-directed protein modifier - Van der Veen, Annemarthe G. (National Academy of Sciences, 2011)
The ubiquitin (Ub)-related modifier Urm1 functions as a sulfur carrier in tRNA thiolation by means of a mechanism that requires the formation of a thiocarboxylate at the C-terminal glycine residue of Urm1. However, whether Urm1 plays an additional role as a Ub-like protein modifier remains unclear. Here, we show that Urm1 is conjugated to lysine residues of target proteins and that oxidative stress enhances protein urmylation in both Saccharomyces cerevisiae and mammalian cells. Similar to ubiquitylation, urmylation involves a thioester intermediate and results in the formation of a covalent peptide bond between Urm1 and its substrates. In contrast to modification by canonical Ub-like modifiers, however, conjugation of Urm1 involves a C-terminal thiocarboxylate of the modifier. We have confirmed that the peroxiredoxin Ahp1 is such a substrate in S. cerevisiae and found that Urm1 targets a specific lysine residue of Ahp1 in vivo. In addition, we have identified several unique substrates in mammalian cells and show that Urm1 targets at least two pathways on oxidant treatment. First, Urm1 is appended to lysine residues of three components that function in its own pathway (i.e., MOCS3, ATPBD3, and CTU2). Second, Urm1 is conjugated to the nucleocytoplasmic shuttling factor cellular apoptosis susceptibility protein. Thus, Urm1 has a conserved dual role by integrating the functions of prokaryotic sulfur carriers with those of eukaryotic protein modifiers of the Ub family.